Adaptive evolution of coagulation and blood properties in hypoxia tolerant Spalax in Israel. (9th June 2017) - Danial‐Farran, N.; Nasser, N. J.; Beiles, A.; Brenner, B.; Sarig, G.; Nevo, E.
Abstract: The subterranean blind mole rat ( Spalax ) is adapted to underground life stresses genomically, proteomically, and phenomically. It has been studied multidisciplinarily as an evolutionary model, and a potential medical therapy resource. The four parapatric species in Israel, are climatically adapted. Here, we examine coagulation, and blood properties of one population in each of the four species . Our results show that Spalax galili possesses the shortest average bleeding time compared to the other Spalax species ( P  < 0.04). Likewise, Spalax galili possesses the shortest average activated partial thromboplastin time. Prothrombin time is 16.34 ± 4.25, 23.3 ± 8.99, 15.71 ± 4.24, and 17.37 ± 6.02 s in Spalax galili, Spalax golani, Spalax carmeli and Spalax judaei, respectively, with significant differences between Spalax galili and Spalax golani, and between Spalax golani and Spalax carmeli populations ( P  < 0.05). Blood hemoglobin is higher in Spalax galili and Spalax golani compared to Spalax carmeli and Spalax judaei populations. Bleeding time, coagulation profiles, and blood properties differ partly between the examined populations. These differences appear adaptive, associated with climatic variation, population density, and the risk of injury during digging, fighting and preying. The population under the highest injury risk displayed the shortest bleeding time. Abstract : The subterranean blind mole rat ( Spalax ) lives its entire life in underground tunnels. Four parapatric species of Spalax exist in Israel, and we examined coagulation and blood properties in one population of each of the four species. Bleeding time, coagulation profiles, and blood properties differed partly between the examined populations, and the population under the highest injury risk displayed the shortest bleeding time.